If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 686 = 7(-8x + -22) Reorder the terms: 686 = 7(-22 + -8x) 686 = (-22 * 7 + -8x * 7) 686 = (-154 + -56x) Solving 686 = -154 + -56x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '56x' to each side of the equation. 686 + 56x = -154 + -56x + 56x Combine like terms: -56x + 56x = 0 686 + 56x = -154 + 0 686 + 56x = -154 Add '-686' to each side of the equation. 686 + -686 + 56x = -154 + -686 Combine like terms: 686 + -686 = 0 0 + 56x = -154 + -686 56x = -154 + -686 Combine like terms: -154 + -686 = -840 56x = -840 Divide each side by '56'. x = -15 Simplifying x = -15
| -3-16b=-3-15b-2b | | -x+6=y | | (3x-5)+(7y)=180 | | 6y=-2+3x | | -18w-17=19-20w | | 7x-2=5x-3+2x-1 | | -2*10-3y=-7 | | 17=3x-2(x-5) | | 2p+2p-3=2p+1 | | -20-6k=-k | | 3x-x+2=22 | | 2x^(1/2) | | 27=y/3-13 | | -2*3-3y=-7 | | 4w-22=8w-70 | | 4x+8x^2=9 | | -17g-4=14-8g | | log(45/x)=0.34 | | -96=-6g+2g | | -2*4-3y=-7 | | 2x-24x=-72 | | -8h+10=-9h+18 | | p^2-2p=-1 | | -9f-6f=24 | | -2*2-3y=-7 | | X^5=65 | | 6=v+5v | | 48=5y-12 | | -3-4z=-15 | | 9x-6=12x-3x | | 3(-2x-1)=2x+5 | | 4(1+5g)= |